2016
DOI: 10.1002/uog.17289
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stillbirth from biochemical and biophysical markers at 11–13 weeks

Abstract: A model based on maternal factors and first-trimester biomarkers can potentially predict more than half of subsequent stillbirths that occur due to impaired placentation. The extent to which such stillbirths could be prevented remains to be determined. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
(19 reference statements)
2
28
0
Order By: Relevance
“…Reports on the capability of PlGF to predict SGA have been conflicting. Initial small case–control studies in the first and second trimesters for the prediction of SGA found no significant relationship, but subsequent larger case–control studies and several prospective cohorts measuring PlGF in the second and first trimesters have reported an association between low PlGF concentrations and early‐onset pre‐eclampsia, stillbirth and SGA. The few small ( n = 21 or fewer), mainly case–control studies in which measurement was undertaken in the third trimester (including at time of delivery), generally concur with our finding of low PlGF concentration in women with subsequent delivery of a SGA infant, particularly those with significant underlying placental pathology.…”
Section: Discussionsupporting
confidence: 80%
“…Reports on the capability of PlGF to predict SGA have been conflicting. Initial small case–control studies in the first and second trimesters for the prediction of SGA found no significant relationship, but subsequent larger case–control studies and several prospective cohorts measuring PlGF in the second and first trimesters have reported an association between low PlGF concentrations and early‐onset pre‐eclampsia, stillbirth and SGA. The few small ( n = 21 or fewer), mainly case–control studies in which measurement was undertaken in the third trimester (including at time of delivery), generally concur with our finding of low PlGF concentration in women with subsequent delivery of a SGA infant, particularly those with significant underlying placental pathology.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies reported that, at 11–13 weeks' gestation, serum PlGF is reduced in pregnancies with impaired placentation resulting in PE or the birth of an SGA neonate. The performance of early screening for stillbirth due to impaired placentation by an algorithm that incorporates serum PlGF is superior to that relying on maternal factors alone or a combination of maternal factors with UtA‐PI, DV‐PIV and serum PAPP‐A. This is not surprising since we have reported previously that, in early screening for PE by a combination of maternal factors and biomarkers, serum PlGF had a better performance than did serum PAPP‐A.…”
Section: Discussionmentioning
confidence: 68%
“…Accurate prediction of term stillbirth and other adverse outcomes that may be prevented from earlier delivery will require a paradigm shift in the assessment of stillbirth risk. Traditional approaches based on maternal risk factors, fetal growth assessments, and ancillary ultrasound tools such as fetoplacental Doppler studies perform poorly for term outcomes compared to preterm outcomes [30][31][32][33][34]. Placental function biomarkers have not yet been clinically useful but are a potential source of benefit in the future [35][36][37].…”
Section: Challenges To the Safe Deferral Of Late Preterm And Early Tementioning
confidence: 99%